Hubungan Dukungan Sosial dengan Kejadian Postpartum Blues pada Ibu Nifas di Wilayah Kerja Puskesmas Pomalaa: The Relationship of Social Support with Postpartum Blues in Postpartum Mothers in the Work Area of Pomalaa Puskesmas - Mariany Mariany; Rosani Naim; Iis Afrianty (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Postpartum blues is a natural response to drastic hormonal changes after giving birth that affect the physical and emotional state of postpartum mothers. These drastic hormonal changes are not the main factor in the occurrence of postpartum blues, but the impact on the mother's psychological life, such as the lack of support from her husband, family, or community, postpartum fatigue, worries about economic conditions, and other social problems. This study aimed to determine the relationship between social support and the incidence of postpartum blues in postpartum mothers in the working area of the Pomalaa Health Center. This type of research is a correlation analytic with a cross-sectional design with a population of 50 postpartum mothers. Data was collected using the Postpartum Depression Predictors Inventory (PDPI) and the Edinburgh Postnatal Depression Scale (EPDS) questionnaire. 12 postpartum mothers experienced postpartum blues (24%). Four received less social support, and 8 people received good social support. There is a relationship between social support and postpartum blues in postpartum mothers in the Pomalaa Health Center working area with a p-value of 0.002. Husbands and families, as the closest people, are expected to be able to provide social support to postpartum mothers so that mothers avoid postpartum blues.